Derivation and validation of four patient clusters in Still's disease, results from GIRRCS AOSD-study group and AIDA network still disease registry - ALİBAZ ÖNER, FATMA (My University, 2023)
Background Different patient clusters were preliminarily suggested to dissect the clinical heterogeneity in Still’s disease. Thus, we aimed at deriving and validating disease clusters in a multicentre, observational, prospective study to stratify these patients. Methods Patients included in GIRRCS AOSD-study group and AIDA Network Still Disease Registry were assessed if variables for cluster analysis were available (age, systemic score, erythrocyte sedimentation rate (ESR), C reactive protein (CRP) and ferritin). K-means algorithm with Euclidean metric and Elbow plot were used to derive an adequate number of clusters. Results K-means clustering assessment provided four clusters based on means standardised according to zscores on 349 patients. All clusters mainly presented fever, skin rash and joint involvement. Cluster 1 was composed by 115 patients distinguished by lower values of age and characterised by skin rash myalgia, sore throat and splenomegaly. Cluster 2 included 128 patients identified by lower levels of ESR, ferritin and systemic score; multiorgan manifestations were less frequently observed. Cluster 3 comprised 31 patients categorised by higher levels of CRP and ferritin, they were characterised by fever and joint involvement. Cluster 4 contained 75 patients derived by higher values of age and systemic score. Myalgia, sore throat, liver involvement and life-threatening complications, leading to a high mortality rate, were observed in these patients. Conclusions Four patient clusters in Still’s disease may be recognised by a multidimensional characterisation (‘Juvenile/Transitional’, ‘Uncomplicated’, ‘Hyperferritinemic’ and ‘Catastrophic’). Of interest, cluster 4 was burdened by an increased rate of life-threatening complications and mortality, suggesting a more severe patient group.